2013
DOI: 10.1111/eje.12027
|View full text |Cite
|
Sign up to set email alerts
|

The creation of virtual teeth with and without tooth pathology for a virtual learning environment in dental education

Abstract: The creation and use of virtual teeth in dental education appears to be feasible but is still in development; it offers many opportunities for the creation of teeth with various pathologies, although an evaluation of its use in dental education is still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 12 publications
(11 reference statements)
0
64
1
Order By: Relevance
“…Group II consisted of students who entered the Dental School in 2012. Both groups of students participated in a 4‐ to 6‐month manual dexterity training during the first year using the MOOG Simodont dental trainer ® , and the training was completed with a test. Group I was required to follow a scheduled training programme and take the manual dexterity test at a fixed date and time decided on by the school.…”
Section: Methodsmentioning
confidence: 99%
“…Group II consisted of students who entered the Dental School in 2012. Both groups of students participated in a 4‐ to 6‐month manual dexterity training during the first year using the MOOG Simodont dental trainer ® , and the training was completed with a test. Group I was required to follow a scheduled training programme and take the manual dexterity test at a fixed date and time decided on by the school.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the conventional physical tooth models traditionally used in dental education, several applications based on virtual tooth models have been proposed for dental training courses [94][95][96][97]. In contrast to these commercial systems, Kato and colleagues [98] recently reported that freely accessible 3D models of teeth embedded into portable document format (PDF) files would constitute a valuable tool for dental students as well.…”
Section: Interactive Three-dimensional Models Of Human Teethmentioning
confidence: 99%
“…These days, dental curricula are often developed in response to an urgent problem. For example, current dental training is facing a major issue regarding the growing scarcity of human extracted teeth and suitable patients with the right dental needs for students’ education . Therefore, on such condition that dental training is dependent on the availability of specific extracted teeth and patients with specific procedures, this scarcity may prevent students from acquiring the necessary skills and competencies within the limited time for training to develop into confident qualified practitioners.…”
Section: Introductionmentioning
confidence: 99%